Identity at the Molecular Level: Advances in Forensic Biology and Human Identification - Nandini Katere (AG Volumes, 2026)
Analyses based on genetic material have been transformed by molecular forensic biology, which allows for the accurate and reliable analysis of DNA. The use of new technologies such as DNA Profiling, short tandem repeat (STR), mitochondrial DNA analysis, single nucleotide polymorphism (SNP) genotyping and rapid DNA systems has enhanced the examination of biological evidence in routine and complex forensic cases. New molecular techniques, including next-generation sequencing, forensic epigenetics, transcriptomics, and microbiome analysis, have also broadened the forensic science toolbox to help with age estimation and tissue identification, or to improve the analysis of degraded or mixed samples. These technologies can be used in crime scene investigation, disaster victim identification, kinship testing, and wildlife forensics. While all of this has been achieved, there are still problems of ethical governance, genetic privacy, laboratory standardization and the interpretation of complex genetic evidence, especially in developing forensic systems like India. Investment in advanced technologies, skilled personnel, accredited laboratories and robust regulatory frameworks will help to further develop molecular forensic biology and facilitate the accurate, ethical and efficient identification of human remains in the criminal justice system.